Insecticides, Miticides and Molluscicides Available to Florida's Floricultural Industry - James F. Price; Curtis Nagle; Elzie McCord, Jr. (EDIS, 2008)
Revised! ENY-679, an 8-page fact sheet by James F. Price, Curtis Nagle, and Elzie McCord, Jr., lists the commercial products currently registered for arthropod and gastropod management in Florida’s commercial production sites, adding to the information available in crop-specific guides. Published by the UF Department of Entomology and Nematology, November 2007.